GENRE KNOWLEDGE AND THE STUDENTS’ ABILITY IN WRITING PARAGRAPH (A STUDY IN SMA NEGERI 1 BULUKUMBA) - Nurhikmah, Andi; Putri, Alfridha Dwi (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2016)
This present study aims at finding out the use of genre knowledge in improving the students’ ability in writing the paragraph. This study was held in SMA Negeri 1 Bulukumba. The method applied was the pre-experimental design that consists of pretest, treatment, and posttest. The result of this study shows the improvement of the students’ ability in writing good paragraphs in terms of organization and vocabulary aspects. The study indicates that there was a significant improvement of the students’ ability to write good paragraphs viewed from two aspects, organization and vocabulary. Conclusion based on the result analysis shows that genre knowledge can improve students’ writing ability.